MARKETING PROMOTIONAL LINGUISTIC CONTENTS: A DISCOURSE ANALYSIS ON TOURISTIC MAGAZINE, LOMBOK-INDONESIA - Basri, Hasan; Zaitun, Zaitun; Rami, Muhammad; Sugandi, Yogi Birul Walid (2021)
Study on the linguistic content of marketing promotion has received a small concern among tourism academicians. This subject, however, contributes a severe impact on customers' decisions, whether or not they approve a purchase or rejection. This paper thoroughly shines a light on the issue of linguistic use in the context of touristic marketing of Gililife magazine in the two published editions. Subsequently, discourse analysis was employed as a method of analysis under the qualitative approach. The data was carefully analyzed in four steps: collecting data, reducing data, displaying data, and drawing a conclusion. The information was collected from selecting four discourses discussing destinations with five main tourism components (attraction, amenity, accessibility, ancillary service, security) as the basis for content analysis. The findings show that the discourses predominantly emphasize attractions and amenities. However, security is being neglected in every lesson, even though it places a robust reason for visits.